Promoting Stair Climbing as an Exercise Routine among Healthy Older Adults Attending a Community-Based Physical Activity Program - Hongu, Nobuko; Shimada, Mieko; Miyake, Rieko; Nakajima, Yusuke; Nakajima, Ichirou; Yoshitake, Yutaka (Sports (Basel), 2019)
Stair climbing provides a feasible opportunity for increasing physical activity (PA) in daily living. The purpose of this study was to examine the daily walking and stair-climbing steps among healthy older adults (age: 74.0 ± 4.9 years; Body Mass Index (BMI): 22.3 ± 2.5 kg/m2). Participants (34 females and 15 males) attended a weekly 6-month community-based PA program. During the entire program period, daily walking and stair-climbing steps were recorded using a pedometer (Omron, HJA-403C, Kyoto, Japan). Before and after the 6-month program, height, body weight and leg muscle strength were assessed. After the 6-month program, the mean walking and stair-climbing steps in both women and men increased significantly (p ≤ 0.01). Daily stair-climbing steps increased about 36 steps in women and 47 steps in men. At the end of 6 months, only male participants had significant correlation between the number of stair steps and leg muscle strength (r = 0.428, p = 0.037). This study reported that healthy older adults attending the community-based PA program had regular stair-climbing steps during daily living. Promoting stair climbing as an exercise routine was feasible to increase their walking and stair-climbing steps.